Brain Volume and Perception of Cognitive Impairment in People With Multiple Sclerosis and Their Caregivers - Fenu, Giuseppe; Lorefice, Lorena; Carta, Elisa; Arru, Mauro; Carta, Alice; Fronza, Marzia; Coghe, Giancarlo; Frau, Jessica; Contu, Franco; Barracciu, Maria Antonietta; Cocco, Eleonora (Frontiers in Neurology, 2021)
Background: Cognitive impairment (CI) is common in multiple sclerosis people (pwMS). The assessment of CI is based on neuropsychological tests’ administration and accurate anamnesis, involving the patients and caregivers (CG). This study aimed to assess the complex interplay between self-perception of CI, objective CI and brain atrophy of MS patients, also exploring the possible differences with the CG’ perceptions. Methods: Relapsing pwMS were enrolled. Subjects were undergone to: neuropsychological examination using the “Brief Cognitive Assessment for Multiple Sclerosis” (BICAMS); evaluation of self-reported cognitive status using the patient-version of the “Multiple Sclerosis Neuropsychological Questionnaire " (p-MSNQ); depression and anxiety evaluation using the “Back depression inventory-version II” (BDI-II) and Zung Anxiety Scale. Thus, brain MRIs images were acquired and brain volumes estimated. For each patient was enrolled a caregiver and collected his perception on the patient's CI using the MSNQ- CG version. Results: 95 MS subjects with their caregivers were enrolled. CI was detected in (51; 53.7%) patients. Pearson test showed a significant correlation of BICAMS T scores with lower whole brain (Rho=0.51), grey matter (Rho=0.54) and cortical grey matter (Rho=0.51) volumes (p<0.001). A relationship of BICAMS T scores with lower p-MSNQ (Rho=0.31) and cg-MSNQ (Rho=0.41) scores was also observed. While no association has been reported between brain volumes and p-MSNQ scores, influenced by BDI-II and Zung scores (p<0.001), an association with lower cg-MSNQ scores was found (p=0.01). Conclusion: Our data confirm brain atrophy as biomarkers of CI. It is also shown the importance of caregiver's perception for cognitive assessment of pwMS.